Culture as a Bubble - Cozzi, Guido (Journal of Political Economy, 1998)
This paper considers an overlapping generations growth model in which “culture” is viewed as a public input in the production process of the labor efficiency units of future generations. Given the low appropriability of its beneficial effects, the market value of culture will be due to bubbles. I shall characterize the balanced growth paths associated with stationary rational bubbles on culture. Indeterminacy arises in the transition dynamics.